LEGAL PROTECTION OF TRADEMARKS: SOLUTIONS FOR SMEs IN PAREPARE CITY - Pikahulan, Rustam Magun; Rasyid, St. Cheriah; Madani, Mutiah Suci (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines legal protection for trademarks of Micro, Small, and Medium Enterprises (MSMEs) in Parepare City. MSMEs in this region play a crucial role in the local economy, yet business actors' awareness of the importance of trademark registration remains low. Lack of knowledge about the benefits of trademark protection and perceptions of high costs and complicated procedures are the main obstacles. This research employs a normative-empirical method, using primary data from interviews with MSME actors and secondary data from legal literature. The findings highlight the need for education, assistance, and improved accessibility to trademark registration services. Education through training and seminars, assistance by legal consultants, and the use of digital systems such as e-filing can enhance awareness and ease the registration process. Trademark protection provides exclusive rights, prevents unfair business competition, and increases the competitiveness of MSMEs. With government support in the form of subsidies or assistance programs, it is expected that MSMEs will be better prepared to face global challenges and ensure business sustainability.